1991
DOI: 10.1038/jcbfm.1991.120
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Sympathetic and Cholinergic Influences on Cerebral Vasodilation Caused by Sciatic Nerve Stimulation in the Rat

Abstract: Summary:We studied the influences of sympathetic and cholinergic mechanisms on pial arteriolar responses dur ing cortical activation in the rat. Adult male Sprague Dawley rats were anesthetized with a-chloralose and ure thane and mechanically ventilated. Pial arterioles on the somatosensory cortex were visualized on a video monitor through a closed cranial window. Changes in arteriolar diameter induced by sciatic nerve stimulation (0. We recently developed a model in the rat in which specific pial arterioles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The presence of such vasodilator neurons has, however, never been convincingly demonstrated. Moreover, alterations of sympathetic and parasympathetic cholinergic mechanisms by superior cervical ganglionectomy, atropine application, and lesioning of cholinergic input did not affect the pial dilator response to sciatic nerve stimulation (7). Pial arterioles may also dilate by a shear stress-dependent mechanism (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such vasodilator neurons has, however, never been convincingly demonstrated. Moreover, alterations of sympathetic and parasympathetic cholinergic mechanisms by superior cervical ganglionectomy, atropine application, and lesioning of cholinergic input did not affect the pial dilator response to sciatic nerve stimulation (7). Pial arterioles may also dilate by a shear stress-dependent mechanism (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, 1995). Although its lesion does not alter the changes in CBF induced by neural activity (Ibayashi et al, 1991), this pathway may contribute to maintain resting CBF and modulate the increases in CBF produced by somatosensory activation (Iadecola et al, 1983; Lecrux and Hamel, 2016; Lecrux et al, 2017). On the other hand, cortical norepinephrine levels, which depend in large part on the noradrenergic innervation from the locus coeruleus, have been shown to increase the vasoconstrictor tone in cerebral cortex and help focus oxygen delivery to the activated areas (Bekar et al, 2012).…”
Section: Neurovascular Couplingmentioning
confidence: 99%
“…Additionally, we have recently shown that there is no local increase in interstitial adenosine in the hindlimb sensory-motor cortex and that the adenosine antagonist 8-sulfophenyltheophylline fails to block the increase in flow associated with sciatic nerve stimulation (34). Furthermore, the local increase in cortical blood flow in response to peripheral nerve stimulation is not mediated through adrenergic or cholinergic receptors (35).…”
Section: Discussionmentioning
confidence: 99%